Analisis Rasio Efektivitas dan Efisiensi Kinerja Keuangan Rumah Zakat Tahun 2024 - Khairina Annisa; Manik Mutiara Sadewa; Nurhidayati (P3M Politeknik Negeri Banjarmasin, 2025)
This research aimed to assess how effectively and efficiently Rumah Zakat managed its finances during the year 2024. Utilizing a descriptive quantitative method, the study analyzed 22 financial ratios derived from the assessment standards developed by PUSKAS BAZNAS, based on audited financial reports for 2024. The results revealed an outstanding level of distribution effectiveness, demonstrated by a Net Allocation to Collection Ratio of 91.31% and a Turn Over Ratio of 10.06. However, this strong effectiveness is contrasted by poor fundraising efficiency, as reflected in a Fundraising Cost Ratio of 108.95%, significantly above the established efficiency benchmark. The disparity between high effectiveness and low efficiency highlighted the need for a strategic overhaul in fundraising efforts through strengthening digitization of systems, collaboration among zakat institutions, and grassroots community involvement. These insights call for an improvement in performance measurement metrics for zakat management organizations (OPZ) and advocate for a governance model that is both sustainable and grounded in sharia-based values.